2022
DOI: 10.1002/ece3.8942
|View full text |Cite
|
Sign up to set email alerts
|

Multiple species delimitation approaches with COI barcodes poorly fit each other and morphospecies – An integrative taxonomy case of Sri Lankan Sericini chafers (Coleoptera: Scarabaeidae)

Abstract: DNA taxonomy including barcoding and metabarcoding is widely used to explore the diversity in biodiversity hotspots. In most of these hotspot areas, chafers are represented by a multitude of species, which are well defined by the complex shape of male genitalia. Here, we explore how well COI barcode data reflect morphological species entities and thus their usability for accelerated species inventorization. We conducted dedicated field surveys in Sri Lanka to collect the species-rich and highly endemic Sericin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 179 publications
1
11
0
Order By: Relevance
“…However, the fact that we found no correlation between species composition (for total assemblage) and geographic distance (Figure 5), even for adjacent localities situated in the same forest type also in the same mountain range (e.g., L2, L4), may indicate either that species generally might tend to disperse also over moderate‐to‐longer distances or that species disperse very little. Limited dispersal is supported further by molecular evidence (Ranasinghe et al, in review; Ranasinghe, Eberle, Thormann, et al, 2022), since different, the same here investigated localities shared almost no haplotypes. This latter conclusion would be not surprising as previous studies have also shown high turnover rates of assemblage composition at higher elevations independently from geographical distance (García‐López et al, 2010).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…However, the fact that we found no correlation between species composition (for total assemblage) and geographic distance (Figure 5), even for adjacent localities situated in the same forest type also in the same mountain range (e.g., L2, L4), may indicate either that species generally might tend to disperse also over moderate‐to‐longer distances or that species disperse very little. Limited dispersal is supported further by molecular evidence (Ranasinghe et al, in review; Ranasinghe, Eberle, Thormann, et al, 2022), since different, the same here investigated localities shared almost no haplotypes. This latter conclusion would be not surprising as previous studies have also shown high turnover rates of assemblage composition at higher elevations independently from geographical distance (García‐López et al, 2010).…”
Section: Discussionsupporting
confidence: 75%
“…Multiple traps from one locality have the same color and colors correspond to Figure S1. molecular evidence (Ranasinghe et al, in review;Ranasinghe, Eberle, Thormann, et al, 2022), since different, the same here investigated localities shared almost no haplotypes. This latter conclusion would be not surprising as previous studies have also shown high turnover rates of assemblage composition at higher elevations independently from geographical distance (García-López et al, 2010).…”
Section: Discussionmentioning
confidence: 59%
“…Sequences were assembled, edited and aligned using Geneious R7 (version 7.1.9, Biomatters Ltd.). All data are deposited in BOLD (project: SCOIB) and GenBank (accession numbers MW698204 -MW698469 (Sericini; Ranasinghe et al, 2022a) and XX-XX, (other taxa; see Table S1)).…”
Section: Dna Sequencingmentioning
confidence: 99%
“…Furthermore, the match ratios for all pairs of delimitation methods were calculated analogously as explained above and compared in a similarity matrix. Subsequently, the matrix was transformed into a distance matrix and a principal coordinate analysis (PCoA) was performed in PAST v.3.25 (Hammer et al, 2001) to visualize the similarity of outcome between the different methods (Ranasinghe et al, 2022a). The same was done for species inventories resulting from individual subclade analyses and cumulated inventories from individually performed species delimitation analyses on subclades, in which entities of each subclade delimitation were taken again together for the entire assemblage, to explore whether species delimitation on subclades alone affected the overall outcome of delimitation analyses.…”
Section: Species Delimitationmentioning
confidence: 99%
See 1 more Smart Citation